Irrigation systems for research farms - Hartley, P.V. (1996)
Irrigation is as old as civilization. Irrigation supplements the water available from rainfall and ground water of the real value of irrigation is not so much in preventing a total as getting Maximum yield if irrigation is for profit, the Increase in crop value due to irrigation must be equal to or more than the cost of the irrigation system. Only good management practices bring good results.